(untitled) (Tanzania Medical Journal, 2025)
Background Africa bears 24% of the global disease burden but is served by only 3% of the world’s health workforce, contributing to the continent's failure to achieve the Millennium Development Goals by 2015. The shortage is particularly acute among frontline health professionals such as nurses and midwives. eLearning has emerged as a promising solution for training in-service health workers, offering flexibility and scalability. This study explores the perceptions of eLearning as an innovative training approach among in-service nurses, midwives, and tutors in Tanzania. Methods A mixed-methods approach was employed using a semi-structured questionnaire comprising demographic questions and Likert-scale items. A total of 106 in-service nurses and midwives and 10 nursing tutors participated in the study. Results Overall, participants expressed positive perceptions of eLearning training approach. Among tutors, 74.3% agreed that eLearning enhanced teaching effectiveness, with over 90% highlighting its potential to expand access, improve efficiency, and necessitate institutional and technological support. Similarly, 79.8% of nurses and midwives reported that eLearning materials and activities supported effective learning. Multivariable logistic regression indicated no statistically significant predictors among tutors; however, favorable trends were noted in perceptions of reduced teaching costs and improved resource access. Among students, being male was associated with significantly lower odds of perceiving eLearning materials as effective (AOR = 0.032), while over 10 years of experience increased the odds of positive perceptions (AOR = 3.3). Students also favored fewer face-to-face lectures and appreciated the diversity of assessment methods in eLearning. Conclusion The study highlights strong support for eLearning as a tool to strengthen the health workforce in Tanzania. However, challenges such as limited digital infrastructure and the need for cost standardization persist. Strategic investments and policy support are essential to optimize eLearning implementation and outcomes in resource-limited settings.